Formulasi dan Evaluasi Pasta Gigi Berbahan Cangkang Keong Sawah (Pila ampullaceae) dengan Variasi Konsentrasi HPMC - Aditama, Agnis; Adifa, Wildan Hanifatul; Muzayanah, Arifatul; Choiroh, Afifahtul; Kusumawardani, Arine Giovani; Wahyuni, Ela; Tasya, Pradiva Julias; Eryani, Mikhania Christiningtyas; Muslikh, Faisal Akhmal (BORNEO JOURNAL OF PHARMASCIENTECH, 2024)
The rice field snail (Pila ampullaceae) is a member of the gastropod class commonly found in freshwater habitats and possesses a hard shell that protects its soft body. The shell of the rice field snail is known to be rich in CaCO3 compounds. In this study, the shell of the rice field snail is formulated into toothpaste as an abrasive material. Toothpaste is a semi-solid preparation that functions to remove dirt from the surface of teeth and maintain dental health. This study aims to determine the effect of hydroxypropyl methylcellulose (HPMC) concentration on the physical and hedonic properties of toothpaste based on rice field snail shell (Pila ampullaceae). Using a one shot case study design, three toothpaste samples with different HPMC concentrations, namely 3%, 4%, and 5%, were evaluated. The preparation evaluation included various physical property tests, such as organoleptic tests, homogeneity, pH, spreadability, viscosity, and foam height, as well as hedonic tests. The results of the study showed that variations in HPMC concentration affected several physical properties, including odor, spreadability, viscosity, and foam height. Among the three formulas tested, Formula 3 with a 5% HPMC concentration was the most preferred by respondents.